Physical characterization and biological tests of bioactive titanium surfaces prepared by short-time micro-arc oxidation in green electrolyte - Zaniolo, Karina M.; Biaggio, Sonia R.; Cirelli, Joni A. [UNESP]; Cominotte, Mariana A. [UNESP]; Bocchi, Nerilso; Rocha-Filho, Romeu C. (IOP Publishing, 2022)
Titanium (Ti) and its alloys are the most used biomaterials in dental and orthopedic implant applications. However, despite the good performance of these materials, implants may fail; therefore, several surface modification methodologies have been developed to increase the bioactivity of the metal surface, accelerating the osseointegration process while promoting improved corrosion performance. In this work, the production of a TiO2 coating on titanium through a short-time micro-arc oxidation (MAO) in a green electrolyte (obtained by a mixed solution of K3PO4 and Ca(CH3COO)2.H2O) is proposed, aiming at obtaining a porous oxide layer with Ca and P incorporation through an environmentally friendly experimental condition. The morphology, chemical composition, crystalline structure, wettability, hardness and bioactivity of the modified Ti surfaces were characterized. The MAO process at 250 V for 1 min in the green electrolyte solution allowed the production of a highly porous oxide surface in the anatase crystalline phase, with effective Ca and P incorporation. Pre-osteoblastic cells were used in in-vitro assays to analyze viability, adhesion, proliferation and ability to perform extracellular matrix mineralization on the Ti surfaces (polished and MAO-treated Ti). The MAO-treated Ti surface exhibited better results in the bioactivity tests, presenting more calcium phosphate precipitates. This surface also presented higher hardness, lower hydrophilicity and better performance in biological tests than the polished surface. The here-reported MAO-treated Ti surface is promising for dental implants, especially in patients having poor bone quality that requires greater stimulation for osteogenesis.
Keywords: biological tests; biomaterial; icro-arc oxidation; modified titanium surface; titanium oxide coating